Accelerated Design of High γ′ Solvus Temperature and Yield Strength Cobalt-Based Superalloy Based on Machine Learning and Phase Diagram - Wang, Cuiping; Chen, Xin; Chen, Yuechao; Yu, Jinxin; Cai, Wensu; Chen, Zhongfeng; Yu, Xiang; Li, Yingju; Yang, Yuansheng; Liu, Xingjun (Frontiers in Materials, 2022)
This paper combines machine learning and phase diagram to accelerate the design of a cobalt-based superalloy with a composition of Co-30Ni-10Al-6Ta (at.%). The results show that Co-30Ni-10Al-6Ta alloy exhibits high γ' solvus temperature (1215 ℃) and high yield strength (1220 Mpa at 25 ℃), which is comparable with commercial nickel-based polycrystalline superalloy M-Mar-247. Besides, the wide processing window and excellent γ' phase stability make it lucrative for further applications at high temperatures. Meanwhile, the alloy design method also provides a new idea for efficiently realizing the preparation of high-performance alloys.